An Inhibition of proliferation of human osteosarcoma cell line (MG63) by ajwain (Trachyspermum ammi L.) plant extract - Anusha, B.; Darshan, V. M. Datta; Andallu, B. (Current Botany, 2024)
Trachyspermum ammi L. (TA), popularly called ajwain, is a well-known spice plant, with fruit pods that are used in Indian traditional medicine. Fruits of this plant were scientifically investigated for medicinal properties, but no studies are reported on the vegetative parts of the plant. Hence, the present investigation is aimed to evaluate the aerial parts of the plant for anti-proliferative and antioxidant effects. Methanolic extract (Me) of TA was subjected to sequential fractionation using the solvents in the increasing order of polarity viz. hexane (He), dichloromethane (Dcm), ethyl acetate (Ea), n-butanol (n-Bu), and water (Aq). Phytochemical analyses, DPPH radical scavenging assay, and in vitro antiproliferative activity on the MG63 osteosarcoma cell line (MTT assay) were performed. Preliminary phytochemical analyses revealed the presence of reducing and non-reducing sugars, amino acids, tannins, phenols, terpenoids, and saponins. Ethyl acetate fraction showed the highest amount of total phenolics (367.90±0.02), followed by n-Bu (287.50±0.04), Dcm (193.56±0.07), Me extract (190.14±0.07), Aq (142.20±0.02) and He (80.74±0.01) fractions. Ethyl acetate fraction exhibited higher DPPH radical scavenging activity (IC50 =116.74 μg/mL) followed by n-Bu (IC50=133.81 μg/mL) fraction with a correlation to the higher amount of phenolics and flavonoids. However, maximum antiproliferative activity was exhibited by hexane fraction on MG 63 human osteosarcoma cell line which can be attributed to the presence of thymol, a monoterpenoid phenol present in ajwain. The current study indicates that the aerial parts of T. ammi Linn. can be considered as potential antioxidants and therapeutic against osteosarcoma.